Pengaruh Problem Based Learning Terhadap Pemahaman Konsep dan Minat Belajar Matematika Siswa di Kelas VIII - Yudistira; Rusdi; Risnawita; Gema Hista Medika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low understanding of mathematical concepts and students' learning interest remain major challenges in mathematics education at the Islamic Junior High School (MTs) level. This study aimed to analyze the effect of the Problem Based Learning (PBL) model on students' understanding of mathematical concepts and learning interest. This research employed a quasi-experimental design with a static group comparison: Randomized Control-Group Only Design. The population comprised 37 eighth-grade students distributed across two classes. A total sampling technique was utilized due to the limited population size. The experimental and control classes were determined through a lottery method, following tests for normality, homogeneity, and equality of means based on daily test scores. Data were collected using an essay test and a questionnaire, and subsequently analyzed using a t-test. The findings revealed that the average scores for concept understanding and learning interest in the experimental class were 68.67 and 78.20, respectively. Meanwhile, the control class achieved average scores of 54.59 and 73.36, respectively. The t-test for concept understanding yielded , and the learning interest questionnaire yielded . These results indicate that Problem Based Learning has a significant effect on students' understanding of mathematical concepts and learning interest.